ANALISIS KINERJA KEUANGAN PT. INDOCEMENT TUNGGAL PRAKASA Tbk, Periode 2016-2020 DENGAN MENGGUNAKAN METODE DU PONT SYSTEM - Apriana Anggrreini Bangun; Christina Dewi Wulandari; Annisa Devi Suryani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study to determine the financial performance of the company PT. Indocement Tunggal Prakasa Tbk, in the 2016-2020 period using the Du Pont System method in terms of Net Profit Margin, Total Assets Turnover, Return On Investment, Equity Multiplier. In this research the author uses secondary data obtained from the official website of PT. Indocement Tunggal Prakasa Tbk. From the results of the study it can be concluded that the financial performance of PT. Indocement Tunggal Prakasa Tbk, the period 2016-2020 is not good, it can be seen from the average value of Net Profit Margin, Total Assets Turnover, Return On Investment, Equity Multiplier, Return On Equity for five years is still below the industry standard value so it can be said that PT. Indocement Tunggal Prakasa has not been efficient in managing finances.